KALIMAT-KALIMAT NEGATIF DALAM LIRIK-LIRIK LAGU MEGHAN TRAINOR - SANGER, VELISA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â Â In this research the writer investigates negative sentences in Meghan Trainorâ€Ÿs song lyrics. This research is entitled â€œNegative Sentences in Meghan Trainorâ€Ÿs Song Lyricsâ€. The objectives of this research are to identify, to classify and to analyze forms of negative sentences and find out forms of negative sentences which are mostly used in Meghan Trainorâ€Ÿs Song Lyrics.Â  This research uses descriptive method. The data were collected from Meghan Trainorâ€Ÿs song lyrics in album Title (2015). All the collected data were analyzed by using the theories of Aarts and Aarts (1982) and Thomson and Martinet (1986).Â  The result of this research shows that there are 63 negative sentences found in Meghan Trainorâ€Ÿs song lyrics. The forms of negative sentences consist of negative sentences which are formed of the word not (48) and negative sentences with negative expression (15). Negative sentences formed of the word not that contains dare, need, and used, and negatif sentence with negative expression none, hardly and hardly ever, are not found in this research. Negative Sentence which is mostly found in Meghan Trainorâ€Ÿs song lyrics is negative sentence formed of the word not with 48 data. Keywords : Negative Sentences, Meghan Trainor Song Lyrics, Descriptive Analysis